Spatial genetic analysis reveals high connectivity of tiger (Panthera tigris) populations in the Satpura–Maikal landscape of Central India. Issue 1 (29th November 2012) - Sharma, Sandeep; Dutta, Trishna; Maldonado, Jesús E.; Wood, Thomas C.; Panwar, Hemendra Singh; Seidensticker, John
Abstract: We investigated the spatial genetic structure of the tiger meta‐population in the Satpura–Maikal landscape of central India using population‐ and individual‐based genetic clustering methods on multilocus genotypic data from 273 individuals. The Satpura–Maikal landscape is classified as a global‐priority Tiger Conservation Landscape (TCL) due to its potential for providing sufficient habitat that will allow the long‐term persistence of tigers. We found that the tiger meta‐population in the Satpura–Maikal landscape has high genetic variation and very low genetic subdivision. Individual‐based Bayesian clustering algorithms reveal two highly admixed genetic populations. We attribute this to forest connectivity and high gene flow in this landscape. However, deforestation, road widening, and mining may sever this connectivity, impede gene exchange, and further exacerbate the genetic division of tigers in central India. Abstract : The Satpura–Maikal landscape is a global‐priority Tiger Conservation Landscape (TCL) that supports 12% of India's tiger population and comprises 13% of tiger habitat in India. Here, we present the findings of our study of the spatial genetic structure and connectivity of tiger populations in Satpura–Maikal landscape of central India. We found that this tiger meta‐population has high genetic variation and very low genetic subdivision due to forest connectivity and high gene flow. However, infrastructural development and exploitation of natural resources poses a threat to the survival of this meta‐population.